Stratifikasi Sosial Dalam Film Zootopia Produksi Walt Disney Pictures - Penti Adisti (Universitas Palangka Raya, 2025)
This study aims to analyze the forms and structure of social stratification portrayed in the animated film Zootopia, produced by Walt Disney Pictures. The film was chosen because it represents societal structures with various social layers through animal characters that reflect human social realities. The type of research used is descriptive qualitative research, with data collection techniques involving observation and note-taking of scenes, dialogues, and narratives that illustrate social class divisions in the film. The study was conducted objectively without comparing it to the real-life society where the film was produced. The theoretical framework used in this study is based on Sorokin's theory, which divides society into three social classes: upper class, middle class, and lower class. Additionally, Soekanto's theory is applied, which classifies social stratification into closed, open, and mixed classes.The results of the study show that Zootopia presents a clear picture of social stratification. The upper class is represented by predators, such as lions and wolves, who hold power and have influential roles in the government. The middle class is symbolized by wealthy mice involved in mafia activities. The lower class consists of herbivores, who are perceived as weak, often discriminated against, and have limited access to power and resources. The film also illustrates an open class system, where certain characters from the lower class—such as Judy Hopps—are able to transcend social boundaries and achieve higher status through effort and merit.